Comparison of metformin and N-acetylcysteine on metabolic parameters in women with polycystic ovarian syndrome - Ali, Hina; Radhakrishnan, Gita; Singh, Alpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome (PCOS) is a common disease that affects up to 10% of women of reproductive age, in which hyperandrogenism (HA), enlarged cystic ovaries, and chronic anovulation often co-exist with obesity, dyslipidemia and insulin resistance (IR). There is a need for an alternative to metformin with minimal side effects to improve insulin sensitivity and correct dyslipidemia in PCOS patients. Methods: It was a prospective, Randomized controlled clinical trial. 116 PCOS patients, 58 each in two groups received either Metformin 500 mg TDS or N-acetylcysteine (NAC) 600 mg TDS for 3 months. Clinical and biochemical parameters contributing to metabolic syndrome (MS) and insulin resistance (fasting blood sugar (FBS), fasting insulin (FI), FBS:FI, HOMA-IR and QUICKI) were assessed at the start and end of the study. Results were compared between the two groups. Results: Both treatment modalities resulted in a significant reduction in number of cases with IR (p=0.001) and MS. Fasting hyperinsulinemia improved in 15 % (p=0.12) and 30% (p=0.001) of patients while 12% (p=0.23) and 18% (p=0.049) improvement was seen in FBS:FI in MET and NAC group respectively. Similarly, improvement in HOMA-IR was 12% (p=0.30) and 32% (p=0.001) in MET and NAC group which is significant with NAC. QUICKI and impaired glucose tolerance showed significant improvement in both the groups with a p-value of 0.04 and 0.006, 0.035 and 0.046 respectively. Significant reduction was seen in triglycerides (p=0.048) in NAC group. Conclusions: NAC is equally efficacious as metformin in improving parameters of insulin resistance and metabolic syndrome with minimal occasional side effects ensuring better compliance for a long-term therapy.